From Islamic Leadership to Ethical Climate and Innovative Work - Novitasari, Dewiana; Radita, Fatrilia Rasyi; Sukriyah, Sukriyah; Jumiran, Jumiran; Asbari, Masduki (International Journal of Social and Management Studies, 2022)
The information age, which opens up the competition space freely and widely, has challenged every business organization, including the manufacturing industry, to hone its competitive advantage. The main icon of competitive advantage is the innovative behavior of every employee. Therefore, the purpose of this study was to examine the effect of Islamic leadership and ethical climate on employee innovative behavior by taking 126 employees in the manufacturing industry in Tangerang Banten Regency using the Simple Random Sampling technique. The analysis of this study uses SEM (Structural Equation Model) with SmartPLS software version 3.0 as a statistical tool. The results of this study indicate that Islamic leadership has a positive and significant effect on the ethical climate, Islamic leadership has a positive and significant effect on the innovative behavior of employees, either directly or indirectly through the mediation of the ethical climate.